The Leaflex™ Catheter – A Novel Device for Treating Calcific Aortic Stenosis – First-in-Human Intra-Operative Assessment of Safety and Efficacy. Issue 3 (3rd May 2020) - Bartus, Krzysztof; Surve, Dipti; Sato, Yu; Halevi, Rotem; Kislev, Yael; Sax, Sharon; Markov, Lena; Golan, Erez; Levy, Ronnie; Halon, David; Litwinowicz, Radoslaw; Kapelak, Bogusław; et al.
ABSTRACT: Background: The Leaflex™ is a novel percutaneous device for restoring calcified aortic valve leaflet mobility by mechanical scoring. To demonstrate the safety and efficacy of the Leaflex™ during surgical aortic valve replacement and examination of excised valve tissue. In a growing elderly population with multiple comorbidities, increasing frailty, and often limited mobility a simple mechanical intervention for severe aortic stenosis (AS) may be appropriate in selected patients as a standalone first intervention. Methods: Five patients with severe AS (including one with fused leaflets) were treated with the Leaflex™ during cardiopulmonary bypass prior to valve excision. Estimated pressure gradient (PG) was assessed by the force required to pull a cone through the valve before and after Leaflex therapy. The change in the estimated aortic valve area (AVA) was then calculated based on the Gorlin equation. The excised aortic leaflets were examined histologically, radiographically and by micro-CT, for leaflet integrity. Results: The Estimated PG based on the pullback force decreased by 75% (±2.7%) and estimated AVA increased by 99% (±11%) across 4 tri-leaflet aortic valves and by 53% and 46%, respectively, in one valve with fused commissures. Micro-CT and histology confirmed ventricular surface integrity at the site of scoring in all five cases. Conclusions: In the intraoperative setting, the Leaflex™ was effective in decreasing estimated PG and increasing estimated AVA with the maintenance of valve tissue integrity. Although the results of the pressure gradient are estimates, these encouraging results support further assessment of the Leaflex™ approach in patients with calcific AS.